Principle Justice in Distribution Wealth : Study Qualitative Perspective “Sharia Economy - Rofiqo Meili Mahera; Muhammad Adnan Azzaki (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Justice in distribution riches in perspective economy sharia is principle fundamentally aimed at For create balance social and economic based on the values of the Qur'an and hadith. Principles This ensure that riches No only concentrated on groups certain but distributed in a way fair For fulfil need all layer society, especially those in need. Instruments sharia such as zakat, infak and waqf become tool important in realize justice this, with focus on equality access to source power, alleviation poverty, and empowerment economy. With to uphold justice distribution, economy sharia No only push material well-being but also strengthens solidarity social, reduce inequality, and create harmony between spiritual and life aspects worldly. Research This aiming For describe Principle Justice in Distribution Wealth: Study Qualitative Perspective Islamic Economics. Research This use type study qualitative with use method data collection with studies library research, reading and collecting theory as well as define return in a way descriptive. Research to reveal that implementation values economy sharia can help reduce inequality wealth and increase welfare collective If supported by appropriate policies and regulations .